Reconstructing Maqasid al-Shariah in determining the hadd for theft: A contextual analysis of QS al-Ma’idah 38 based on asbabun nuzul - Muzaqky Muthahhari; Zul Azmi; Hidayatullah Ismail (Priviet Social Sciences Journal, 2025)
The determination of the Hadd for theft in QS al-Ma’idah:38 has long been a point of contention between legal textualism and social reality. This verse is often understood literally, without considering the socio-historical context of the revelation. This article aims to reconstruct the normative meaning of the verse through an analysis of Asbabun Nuzul and the Maqasid al-Shariah approach to reaffirm substantive justice in Islamic law. This study employs a qualitative–descriptive method based on library research, using comparative analysis of classical exegesis (al-Ṭabarī, Ibn Kathīr, al-Qurṭubī) and reformist-modern exegesis (Ibn ‘Āshūr, Rashīd Riḍā, Jasser Auda). The findings show that the Hadd is not intended merely as a punitive instrument but as a moral symbol to safeguard social stability once distributive justice is established. This normative reinterpretation affirms that implementing the Hadd without fulfilling social justice contradicts the Maqasid of Islamic law. In conclusion, authentic Islamic law is not a system of punishment but a divine moral system aimed at honoring human beings and manifesting God’s mercy in social life.